MONITORING OF DROUGHT-VULNERABLE AREA IN JAVA ISLAND, INDONESIA USING SATELLITE REMOTE-SENSING DATA - Roswintiarti, Orbita; Sofan, Parwati; Anggraini, Nanin (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2011)
The impact of climatic variability and climate change is of great importance in Indonesia. Monitoring this impact, furthermore, is essential to the preparedness of the regions in dealing with drought-vulnerable conditions. In this study, satellite remote sensing data were used for monitoring drought in Java island, Indonesia. Monthly rainfall data from Tropical Rainfall Measuring Mission (TRMM) data were used to derive the Standardized Precipitation Index (SPI). The Moderate Resolution Imaging Spectroradiometer (MODIS) onboard the Terra and Aqua satellites was used for calculating the Enhanced Vegetative Index (EVI) and Land Surface Temperature (LST). EVI and LST were then converted to the Vegetation Condition Index (VCI) and the Temperature Condition Index (TCI), which are useful indices for the estimation of vegetation moisture and thermal conditions, respectively. Vegetation Health Index (VHI) was calculated using the VCI and TCI to represent the overall vegetation health. The analysis was carried out during the El Niño/Southern Oscillation (ENSO) of June to August 2009. From the SPI analysis, it is found that since June 2009 the conditions of mild drought (-1.0 < SPI < 0) have developed in almost all parts of Java island due to rainfall deficiency. The VCI maps show that the vegetative stress (VCI < 36) as a result of the vegetation moisture condition has gradually developed in the East Java province in June 2009. Meanwhile, from the TCI maps it is found that the vegetative stress (TCI < 36) due to the thermal condition of vegetation was built up in the West Java province in June 2009. Hence, the overall vegetative health in Java island obtained from the VHI maps shows that the moderate vegetative drought (VHI < 36) started to develop in July 2009.